The disintegrin and metalloprotease Meltrin from Drosophila forms oligomers via its protein binding domain and is regulated by the homeobox protein VND during embryonic development. - Meyer, H.; Von Ohlen, T.; Panz, M.; Paululat, A. (Insect Biochemistry and Molecular Biology, 2010)
A Disintegrin And Metalloprotease (ADAM) proteins belong to the metzincin superfamily of metalloproteases that are known to play important roles in several physiological and developmental processes including myoblast fusion, tumor necrosis factor-? release or fertilization. They are characterized by a typical domain structure with a proteolytically active domain and the protein binding domains both facing the extracellular space. Regulatory mechanisms are largely unknown. Here we report on the potential of the Drosophila ADAM Meltrin to form oligomers via its substrate binding domain. Significantly, oligomerization occurs apparently in a redox-dependent manner. Further analysis revealed that the ACR domain is responsible for aggregation while the disintegrin-like and EGF-like domains are not capable of oligomer formation. Stage dependent transcript analysis revealed a constant expression of three different splice variants, two of which were characterized by sequencing. Like many other ADAM proteins, Meltrin shows a highly restricted expression pattern during embryogenesis with at least two of the respective transcripts being present in a subpopulation of neuronal cells in the embryonic central nervous system. Finally, we report on the identification of the first regulator of meltrin: the homeobox protein ventral nervous system defective specifically excludes Meltrin expression from the embryonic ventral neuroectoderm.